Double mitral valve orifice in atrioventricular defects. Issue 1 (January 1983) - Warnes, C; Somerville, J
Abstract : Eleven patients with double mitral valve orifice and atrioventricular defects were studied, and the diagnosis proven by open heart surgery. The correct preoperative diagnosis was suggested by a characteristic angiographic appearance of the medial border of the left ventricle. M-mode echocardiography may show the two orifices which are better seen on two dimensional echocardiography. Two operative deaths occurred in patients with a slightly obstructive valve, and one late death followed mitral valve replacement. Eight patients did well after minor repair to a cleft, or leaving the valve untouched. Occasionally a double mitral orifice, if disorganised and slightly stenotic, may cause early deterioration in a patient with an otherwise uncomplicated ostium primum defect. The surgeon should be forewarned of this mitral anomaly since simple repair may be difficult.